FAM49B, restrained by miR-22, relieved hepatic ischemia/reperfusion injury by inhibiting TRAF6/IKK signaling pathway in a Rac1-dependent manner. (March 2022) - Huang, Zuotian; Pu, Junliang; Luo, Yunhai; Fan, Jing; Li, Kaili; Peng, Dadi; Zong, Kezhen; Zhou, Baoyong; Guan, Xiangdong; Zhou, Fachun
Abstract: Hepatic ischemia/reperfusion (I/R) injury plays a pivotal pathogenic role in trauma, hepatectomy, and liver transplantation. However, the whole mechanism remains undescribed. The objective of this study is to investigate the internal mechanism by which microRNA-22 (miR-22) targets family with sequence similarity 49 member B (FAM49B), thus aggravating hepatic I/R injury. Here, we found that miR-22 was upregulated while FAM49B was reduced in hepatic I/R injury. Inhibition of miR-22 in vitro was able to intensify expression of FAM49B, thus reducing phosphorylation of inhibitors of nuclear factor kappa-B kinase (IKK) and downstream pro-inflammatory proteins. A dual luciferase reporter assay indicated that miR-22 directly targeted FAM49B. Remission of hepatic pathologic alterations, apoptosis, and release of cytokines derived from constraints of miR-22 were abolished in vivo by repressing FAM49B. Further interference of Ras-related C3 botulinum toxin substrate 1 (Rac1) reversed the function of FAM49B inhibition, thus achieving anti-inflammatory consequences. Graphical Abstract: ga1 Highlights: miR-22 targets FAM49B in hepatic IRI. FAM49B inhibits TRAF6 ubiquitination. miR-22/FAM49B axis functions via Rac1.